Coordination Effects and Optimal Policy Choices of Macroprudential Policy and Monetary Policy - Haifeng Pan; Dingsheng Zhang (Complexity)
Considering three monetary policy rules, together with two endogenous macroprudential policies that are credit constraints (loan to value, LTV) for households and counter-cyclical capital (capital requirement ratio, CRR) for bankers, this paper establishes a dynamic stochastic general equilibrium (DSGE) model. Based on the welfare analysis of different combinations of macroprudential rules and monetary policy rules, this paper identifies the optimal policy combinations and analyzes the coordination effects between macroprudential policies and monetary policies. The results show that no matter what kind of monetary policy rules is implemented, the introduction of macroprudential rules has improved the level of total social welfare. In the optimal “two pillars” framework of monetary policies and macroprudential rules, the main objective of monetary policy is to stabilize price inflation, and the macroprudential policy to be implemented is the CRR macroprudential policy. This combination can effectively promote the stability of the real estate market, financial market, and macroeconomy, while maximizing the improvement of total social welfare.